Omentectomy for apparent early-stage uterine serous carcinoma: a large retrospective cohort study - Zhang, Ouling; He, Yuedong; Zheng, Ai; Xu, Yu (Frontiers in Oncology, 2025)
ObjectivesThis study aims to compare the effects of different omental assessment methods (omentectomy and omental biopsy) on the long-term prognosis of apparent early-stage uterine serous cancer (USC).MethodsA total of 255 women with clinical early-stage USC were included. They were divided into the omentectomy group and the omental biopsy group. The Kaplan-Meier method and the log-rank test were employed to estimate and compare overall survival and disease-free survival between groups. The Cox proportional hazards regression model was used to adjust for potential confounding factors.ResultsWhen compared with undergoing omentectomy, women with apparent early-stage USC who underwent omental biopsy had a deteriorated 5-year OS (HR: 1.76, 95% CI: 1.07-3.52, P=0.009) and 5-year DFS (HR: 1.72, 95% CI: 1.15-2.86, P=0.012). After adjusting for confounding factors, omental biopsy was independently associated with worsening long-term prognosis in apparent early-stage USC (For DFS, aHR=1.78, 95% CI: 1.13-3.20, P=0.025; For OS, aHR=1.68, 95% CI: 1.11-2.75, P=0.041).ConclusionsFor apparent early-stage USC, in terms of long-term survival outcomes, omentectomy is superior to omental biopsy.